Teaching innovation in international relations: professional spaces as a learning field - Bernabé Fraguas, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The Degree in International Relations at the Complutense University of Madrid applies the use of innovative tools in the practical part of some subjects in order to bring some workspaces closer to the students. This article analyses the tools that were articulated through two teaching innovation projects approved in competitive calls: the implementation of awareness-raising campaigns through social networks and websites, participation in the design and implementation of real development cooperation projects, and the writing a book published by a prestigious university.